Role of PPARs in Trypanosoma cruzi Infection: Implications for Chagas Disease Therapy - Eugenia Hovsepian; Federico Penas; Gerardo A. Mirkin; Nora B. Goren (PPAR Research)
Chagas disease, which is caused by Trypanosoma cruzi (T. cruzi), remains a substantial public health concern and an important cause of morbidity and mortality in Latin America. T. cruzi infection causes an intense inflammatory response in diverse tissues by triggering local expression of inflammatory mediators, which results in the upregulation of the levels of cytokines and chemokines, and important cardiac alterations in the host, being one of the most characteristic damages of Chagas disease. Therefore, controlling the inflammatory reaction becomes critical for the control of the proliferation of the parasite and of the evolution of Chagas disease. The nuclear receptors known as peroxisome proliferator-activated receptors (PPARs) have emerged as key regulators of lipid metabolism and inflammation. The precise role of PPAR ligands in T. cruzi infection or in Chagas disease is poorly understood. This review summarizes our knowledge about T. cruzi infection as well as about the activation of PPARs and the potential role of their ligands in the resolution of inflammation, with the aim to address a new pharmacological approach to improve the host health.